Can caregivers' mental disorders be associated with childhood obesogenic eating behavior? - Paulinia Leal do Amaral; Karen Jansen; Suelen de Lima Bach; Amanda Neumann Reyes; Thais Martins-Silva; Ricardo Azevedo da Silva; Janaina Vieira dos Santos Mota; Fernanda Pedrotti Moreira (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objective: to assess the association between caregivers' mental disorders and schoolchildren's obesogenic eating behavior. Methods: cross-sectional study used a public school-based sample of children and their primary caregivers. Caregivers had to report depressive episodes or generalized anxiety disorder (GAD) during the Mini-International Neuropsychiatric Interview (MINI). Children's obesogenic eating behavior were assessed using food responsiveness (FR) and emotional overeating (EOE) subscales of the Children's Eating Behaviour Questionnaire (CEBQ). Bivariate analysis was conducted using the t-test, ANOVA, Pearson correlation, and adjusted linear regression model was used (including variables caregivers: sex, age, economic indicator, and schooling; schoolchildren: sex and nutritional status). Results: study includes 596 children-caregiver dyads (309 boys and 287 girls). Among caregivers, 24.7% had experienced current depressive episodes, 38.7% had past depressive episodes, and 17.2% had GAD. We observed, after adjusted analysis, that having a caregiver in a current depressive episode, increases schoolchildren's obesogenic behavior of, for FR at 0.235 points (β=0.235; CI95%=0.022-0.449;) and EOE at 0.337 points (β=0.337; CI95%=0.162-0.512). Conclusion: caregivers' current depressive episodes were associated with higher averages of obesogenic eating behavior (caregiver-reported), both in consuming palatable food without feeling hungry (FR) and in increasing food intake in response to negative emotions (EOE).